Qualitative Inquiry in Nature-Based Tourism: A Case of Business Crisis Recovery at PT Satwa Sumatera Ecolodges - Mariskova, Devina; Anggoro, Yudo (Universitas Airlangga, 2025)
Background: Until 2019, the tourism sector consistently contributed to Indonesia's GDP, establishing itself as a key economic driver. However, the COVID-19 pandemic severely impacted the tourism industry, causing a sharp decline in GDP contribution and resulting in millions of job losses. PT Satwa Sumatera Ecolodges (Satwa) exemplifies the struggles of the nature-based tourism sector during this period. Founded in 2007, Satwa, located adjacent to Way Kambas National Park (WKNP) in Lampung Timur, offers eco-lodging and tours of the park's natural and wildlife attractions. The prolonged closure of WKNP triggered a financial crisis for Satwa, leading to significant business challenges. Objective: This case study aims to examine Satwa's resilience to external challenges. The research delves into how Satwa, a tourism business, has managed to navigate and withstand the adverse effects brought about by external factors. This study hopes to contribute to the works on tourism resilience and offers insights for similar businesses facing external disruptions. Method: Employing qualitative case study approach, semi-structure interviews and focus group discussions were conducted to gather primary data. The primary data collected from interviews and focus group discussions were thematically analyzed and coded for qualitative interpretation. Cross-method triangulation was applied to confirm interview and FGD outcomes using site visits, observations, internal documentations, and literatures. Results: The findings highlight the company’s commitment to exclusively hiring local staff was found to be crucial for its survival. Conclusion: The tourism industry is notably prone to shifts in external conditions, with the COVID-19 pandemic creating a major crisis for businesses within this sector. Nature-based tourism is especially impacted due to its reliance on natural attractions. However, such crises can also encourage businesses to develop resilience and innovation. In particular, this example shows that supporting local communities can provide a solid basis for overcoming external challenges, demonstrating how community empowerment can promote resilience as the basis for innovation. Keywords: Ecotourism, Ecolodge, Nature-based Tourism, Resilience, Crisis Mitigation